Avaliação da vulnerabilidade em áreas de risco: um estudo de caso da vila Schirmer, Santa Maria, RS. - Cardias, Marcia Elena de Mello (2016)
The Municipal Plans Risk Reduction address a number of technical and management guidelines that allow municipal public authorities to disaster risk reduction. The methodology of evaluation of vulnerability in these instruments only considers sóciourbanísticas variables, however, it is known that the understanding of the social and cultural variables are fundamental to consolidate and organize groups aiming to plan more lasting resilience strategies. This research aims to: assess the vulnerability in risk areas of Vila Schirmer, city of Santa Maria / RS, considering the sóciourbanísticas, social and structural and socio-cultural components. The methodological procedures involved literature review, field work to update the risk zoning and application of semi-structured questionnaires in the risk of housing and comparison sector, out of it. In 2006, there were 26 homes at risk of flooding or landslides in the village, were currently identified 21 new housing which means an increase of 91%. The Sóciourbanísticas components showed that the risk sectors constructive standard of housing is lower than in the comparison, the streets are dirt, there is garbage in the yards of houses and streets and open sewers, setting a more precarious urban infrastructure. The socio-structural components show that the risk sectors families are more numerous, poorly educated, often with informal jobs, where the monthly income is also very low. Already Sociocultural components showed that the risk population has a network of "weak" sociability and as a result has little support from their peers, and limited participation in decision-making regarding risk communities. What is realized in this study was the gap between state vision, based exclusively on the technical aspects of disasters and experiences, sociocultural risk areas residents. So that effectively the risk mappings are put into practice is necessary that along with the technique is contemplated social.